Clinical Relevance of Changes in Pain Intensity in Patients with Specific Back Pain - Haase, Ingo; Kladny, Bernd (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background Pain intensity is frequently measured on the 11-point numerical pain rating scale (NRS-PI), ranging from 0 (no pain) to 10 points (worst imaginable pain). However, it is difficult to interpret the clinical importance of changes from baseline to endpoint on this instrument.Objectives To estimate the minimal detectable change (MDC) and the minimal clinically important difference (MCID) for average pain intensity in patients with specific back pain.Materials and Methods Data on 1232 subjects with specific back pain from a German hospital were included in this study. A score combining the patientʼs (PGIC) and the physicianʼs global impression of change (CGIC) over the in-patient length of stay was used as an external criterion. A priori, we considered the score value “slightly improved” as the MCID. MDC was calculated using the standard error of measurement (SEM) and the standard deviation (SD) of the sample. MCID was estimated by the mean value of PI-NRS change in patients who self-assess as “slightly improved”, and by sensitivity/specificity analyses, computed by the receiver operating characteristic method (ROC).Results MDC was 1.77. The MCS and ROC methods consistently showed an MCID of 2 for the total sample. Both methods showed the dependence of the MCID on the initial pain: 1 for mild to moderate pain at baseline (1 – 4 NRS points), 2 for moderate to severe pain (5 – 7) and 3 – 4 for very severe to extreme pain (8 – 10). For patients with lumbosacral intervertebral disc disorders and patients in the acute phase (duration of pain < 6 weeks), the ROC method resulted in a higher limit than the MCS method.Conclusions In order to facilitate the interpretation of changes and to take into account the patientʼs perspective, the global assessment of the success of treatment should be used as an anchor criterion. In addition to dealing with pain measurement, function-related and psychosocial aspects of pain symptoms should be kept in mind.Hintergrund Schmerzstärke wird häufig mit numerischen Ratingskalen (NRS) gemessen, deren Spannbreite von 0 (kein Schmerz) bis 10 (maximal vorstellbarer Schmerz) reicht. Schwer zu interpretieren ist die klinische Relevanz einer Veränderung zwischen 2 Messzeitpunkten.Ziel Schätzung des kleinsten nachweisbaren Unterschieds (minimal detectable change – MDC) und des kleinsten klinisch relevanten Unterschieds (minimal clinically important difference – MCID) in der Reduktion von durchschnittlicher Schmerzintensität bei Patienten mit spezifischen Rückenschmerzen.Material und Methoden Datensätze von 1232 Patienten mit spezifischen Rückenschmerzen aus einer deutschen Klinik für konservative Krankenhausbehandlung von Wirbelsäulenbeschwerden wurden ausgewertet. Als Ankerkriterium diente eine Kombination aus den Globalurteilen von Patienten und Arzt am Ende der Behandlung. Die Ankerkategorie „etwas gebessert“ betrachteten wir a priori als kleinstes klinisch relevantes Ergebnis. Der MDC wurde mithilfe des Standardmessfehlers (SEM) und der Standardabweichung (SD) der Stichprobe berechnet. Der MCID wurde über die mittlere Schmerzreduktion der „etwas gebesserten“ Patienten (Mean Change Score – MCS) und mittels der Receiver-Operating-Characteristic-Methode (ROC) geschätzt.Ergebnisse Der MDC lag bei 1,77. Der MCS und die ROC-Methode ergaben übereinstimmend eine MCID für das Gesamtkollektiv von 2. Beide Methoden zeigten die Abhängigkeit des MCID vom Ausgangsschmerz: 1 für geringen bis mäßigen Schmerz bei Behandlungsbeginn (1 – 4 NRS-Punkte), 2 für mittleren bis starken Schmerz (5 – 7) und 3 – 4 für sehr starken bis extremen Ausgangsschmerz (8 – 10). Für Patienten mit lumbalen Bandscheibenschäden und Patienten in der akuten Phase ergab die ROC-Methode einen höheren Grenzwert als die MCS-Methode.Diskussion Die globale Einschätzung des Behandlungserfolgs sollte als Ankerkriterium neben der Verlaufsmessung mit NRS verwendet werden, um die Interpretation von Veränderungen zu erleichtern und dabei die Patientenperspektive zu berücksichtigen. Neben der Beschäftigung mit der Schmerzmessung dürfen funktionsbezogene und psychosoziale Aspekte der Schmerzsymptomatik nicht aus dem Blickfeld geraten.
Keywords: specific back pain; pain measurement; numeric pain rating scale; minimal clinically important difference